Anteroposterior axis of the tibia for kinematic aligned total knee arthroplasty - Seikai Toyooka; Noriaki Arai; Hironari Masuda; Hirotaka Kawano; Takumi Nakagawa (Journal of Experimental Orthopaedics)
Abstract Purpose It is not known where the anatomical axis of rotation on the tibial side will be in kinematic alignment (KA), a rapidly expanding area of total knee arthroplasty (TKA) alignment technique today. The purpose of this study was to define the tibial axis for KA‐TKA. Methods Fifty patients who underwent computed tomography (CT) examination of the lower extremities at a single institution were included. The posterior condylar axis (PCA) and surgical epicondylar axis (SEA) were identified in the CT axial view and projected onto the tibial slice. The respective perpendicular lines that pass through was attachment of the posterior cruciate ligament (PCL) were identified as the anatomic axis of rotation of the tibia relative to the PCA and SEA, and the position of each axis of rotation. Furthermore, the relationship of these perpendicular lines with the Akagi line was evaluated. Results The axis of tibial rotation to the SEA was similar to that of the Akagi line; the axis of tibial rotation to the PCA was located approximately 2.9° medial to the Akagi line, and when the origin of the tibial axis was set at the PCL attachment site, the intersection point of the tibial axis was approximately 2.5 mm medial to the medial border of the tibial tuberosity. The distribution of tibial axis had a wide range. Conclusion Although there is a large individual variation, the average tibial axis for KA‐TKA is 2.9° more internally rotated than the Akagi line. Level of Evidence Level IV.